2022
DOI: 10.3389/fbioe.2021.744659
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Signature for Survival Prediction and Immune Implication Based on SARS-CoV-2–Related Genes in Kidney Renal Clear Cell Carcinoma

Abstract: Kidney renal clear cell carcinoma (KIRC) is a common aggressive malignancy of the urinary system. COVID-19, a highly infectious and severe disease caused by SARS-CoV-2, has become a significant challenge for global public health. Cancer patients have been reported to be more vulnerable to SARS-CoV-2 infection and have a higher risk for serious complications than the general population. However, the correlation between KIRC and COVID-19 remains incompletely elucidated. In this study, we comprehensively investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…With a view to the significance of the immune system in antiviral and antitumor responses, we calculated the proportion of different types of tumor-infiltrating immune cells in BRCA using CIBERSORT and used ESTIMATE to explore IS, SS, and tumor purity. Higher SSs and ISs were observed in high-risk patients, leading to an unfavorable prognosis, which was consistent with a line of evidence from previous research ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…With a view to the significance of the immune system in antiviral and antitumor responses, we calculated the proportion of different types of tumor-infiltrating immune cells in BRCA using CIBERSORT and used ESTIMATE to explore IS, SS, and tumor purity. Higher SSs and ISs were observed in high-risk patients, leading to an unfavorable prognosis, which was consistent with a line of evidence from previous research ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although there have been advances in multiple therapeutic methods, including surgery, chemotherapy, and immunotherapy, the prognosis of KIRC patients remains a major clinical challenge because of the high incidence of recurrence and metastasis. As reported, the recurrence rate of KIRC after curative nephrectomy is approximately 20-30% within 5 years (Huang et al, 2021). More importantly, studies have shown that the 5-year overall survival rate is less than 10% in metastatic KIRC patients (Xing et al, 2020;Lamprou et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…ACADM is believed to be one of the important enzymes participated in amino acid metabolism of colon cancer tumor-associated macrophages (TAMs), and the elevated level of ACADM is linked with a more favorable outcome for colon cancer individuals [ 42 ]. In a study of prognostic features of renal cancer according to SARS-CoV-2 related genes, a model constructed with ACADM as one of the hub genes was linked with infiltration of multiple cells of immunity [ 43 ]. According to the findings of our study, ACADM was associated with the infiltration of a number of different immune cells, including Treg cells.…”
Section: Discussionmentioning
confidence: 99%